Madrid, a Bilingual Community: a view from the classroom - Woore, R (2015)
In this brief report, I begin by providing a brief overview of the educational context within which the schools I visited were operating, followed by an outline of the nature of my visit. I then describe some of the key things that struck me in the lessons that I observed and in my conversations with teachers, head teachers, English language assistants and regional ministry officials. The report focuses mainly on the nature of students’ learning, both of English as an L2 and within other academic subject areas; the pedagogical approaches taken; and some of the successes and challenges of teaching through English as experienced at the school level. Finally, I suggest some avenues that future research projects might seek to explore, in order to gain a deeper understanding of some of the key issues involved as I perceived them.